DEVELOPMENT AND CHARACTERIZATION OF POLYMERIC NANOPARTICULATE DELIVERY SYSTEM FOR EXEMESTANE - MH KANANI; KR VADALIA (International Journal of Pharma and Bio Sciences, 2015)
Exemestane is oral- steroidal Aromatase inhibitors. EXE chemotherapy treatment is often associated with a number of drawbacks, like nonselective distribution, early drug degradation, undesirable side effect. However, alternative formulations are needed to overcome the serious side effects, and to improve clinical efficacy of the drug. The aim of this work was to prepare poly-Æ-caprolactone nanoparticle of Exemestane by nanoprecipitation and to characterize them. Percentage of drug (with respect to polymer) was selected as formulation variable. Nanoparticles of Exe were obtained with high encapsulation efficiency. The particle size range was about 37.81–319.9 nm and carried an overall negative surface charge. FT-IR and DSC study indicated no drug and polymer interaction. SEM and TEM image shows non-aggregated and spherical shaped NPs. Percentage of drug significantly influenced particle size, entrapment efficiency and release. The system sustained release of EXE significantly and further investigation could exhibit its potential usefulness in breast cancer therapy.